Emerging Evidence of Macrophage Contribution to Hyperinnervation and Nociceptor Sensitization in Vulvodynia - Barry, Christine Mary; Matusica, Dusan; Haberberger, Rainer Viktor (Frontiers in Molecular Neuroscience, 2019)
Vulvodynia is an idiopathic chronic pain disorder and a leading cause of dyspareunia, or pain associated with sexual intercourse, for women. The key pathophysiological features of vulvodynia are vaginal hyperinnervation and nociceptor sensitization. These features have been described consistently by research groups over the past 30 years, but currently there is no first-line recommended treatment that targets this pathophysiology. Instead, psychological interventions, pelvic floor physiotherapy and surgery to remove painful tissue are recommended, as these are the few interventions that have shown some benefit in clinical trials. Recurrence of vulvodynia is frequent, even after vestibulectomy and questions regarding etiology remain. Vestibular biopsies from women with vulvodynia contain increased abundance of immune cells including macrophages as well as increased numbers of nerve fibers. Macrophages have multiple roles in the induction and resolution of inflammation and their function can be broadly described as pro-inflammatory or anti-inflammatory depending on their polarization state. This state is not fixed and can alter rapidly in response to the microenvironment. Essentially, M1, or classically activated macrophages, produce pro-inflammatory cytokines and promote nociceptor sensitization and mechanical allodynia, whereas M2, or alternately activated macrophages produce anti-inflammatory cytokines and promote functions such as wound healing. Signaling between macrophages and neurons has been shown to promote axonal sprouting and nociceptor sensitization. This mini review considers emerging evidence that macrophages may play a role in nociceptor sensitization and hyperinnervation relevant to vulvodynia and considers the implications for development of new therapeutic strategies.